Coenogonium coronatum (Ostropales: Coenogoniaceae), a new foliicolous species from Thailand, ecological aspects and a key to the species occurring in the country - Neuwirth G. (American Bryological and Lichenological Society Inc., 2014)
Coenogonium coronatum, a lichen-forming ascomycete, is presented and described as new to science. The species differs distinctly from other taxa by the formation of a crustose, smooth thallus and the densely pilose apothecia margins. Photographs of thallus morphology and apothecial anatomy illustrate the new species from the palaeotropics. A key to the Coenogonium species known from Thailand is also included. © 2014 The American Bryological and Lichenological Society, Inc.